What is Religion?, Origins, Definitions, and Explanations. - Idinopulos; Brian C. Wilson (Editors) (Numen Book Series, 1998)
What is Religion? consists of fourteen essays written by a selection of scholars who represent a wide spectrum of approaches to the acedamic study of religion. Each of the essays is an effort not only to take stock of the present controversy concerning appropriate methodologies for the study of religion, but also to take one giant step beyond that to formulate a precise definition of religion. Given the considerable confusion today about what it is exactly that religious studies scholars take to be their subject matter when they presume to professionally teachabout religion, this volume provides a much needed forum for leading scholars to debate and clarify what professors of religious studies understand as the central object or objects under their scrunity.